The Immunoregulatory Role of the Signal Regulatory Protein Family and CD47 Signaling Pathway in Type 1 Diabetes - Sharp, Robert C.; Brown, Matthew E.; Shapiro, Melanie R.; Posgai, Amanda L.; Brusko, Todd M. (Frontiers in Immunology, 2021)
Background The pathogenesis of type 1 diabetes (T1D) involves complex genetic susceptibility that impacts pathways regulating host immunity and the target of autoimmune attack, insulin-producing pancreatic β-cells. Interactions between risk variants and environmental factors result in significant heterogeneity in clinical presentation among those who develop T1D. Although genetic risk is dominated by the human leukocyte antigen (HLA) class II and insulin (INS) gene loci, nearly 150 additional risk variants are significantly associated with the disease, including polymorphisms in immune checkpoint molecules, such as SIRPG. Scope of Review In this review, we summarize the literature related to the T1D-associated risk variants in SIRPG, which include a protein-coding variant (rs6043409, G>A; A263V) and an intronic polymorphism (rs2281808, C>T), and their potential impacts on the immunoregulatory signal regulatory protein (SIRP) family:CD47 signaling axis. We discuss how dysregulated expression or function of SIRPs and CD47 in antigen-presenting cells (APCs), T cells, natural killer (NK) cells, and pancreatic β-cells could potentially promote T1D development. Major Conclusions We propose a hypothesis, supported by emerging genetic and functional immune studies, which states a loss of proper SIRP:CD47 signaling may result in increased lymphocyte activation and cytotoxicity and enhanced β-cell destruction. Thus, we present several novel therapeutic strategies for modulation of SIRPs and CD47 to intervene in T1D.